Signaling by innate immune receptors - Karin, Michael (Henry Stewart Talks, 2009)
Understanding how receptors involved in the detection of infection (TLRs and NLRs) and inflammation (TNFRs) mediated their biological effects, The activation of innate immune responses depends on recognition of infectious organisms (bacteria, fungi, viruses, etc.) by specialized pattern recognition receptors that include the large families of membrane-associated TLRs and cytosolic NLRs, Signaling mechanisms used by TLRs and NLRs, as well as by TNFRs that respond to pro-inflammatory cytokines, Their biological effects include the production of cytokines, chemokines, anti-microbial peptides and enzymes that generate inflammatory mediators and reactive oxygen